2000
DOI: 10.1124/mol.58.5.1017
|View full text |Cite
|
Sign up to set email alerts
|

The Essential Role of Phosphatidylinositol 3-Kinase and of p38 Mitogen-Activated Protein Kinase Activation in the Antioxidant Response Element-Mediated rGSTA2 Induction by Decreased Glutathione in H4IIE Hepatoma Cells

Abstract: The protective adaptive response to electrophiles and reactive oxygen species is mediated by the enhanced expression of the phase II detoxifying genes through antioxidant response elements (AREs). The current study was designed to identify the signaling pathways responsible for the expression of rGSTA2 in response to cellular oxidative stress and to establish the molecular mechanistic basis. Deprivation of cystine and methionine caused oxidative stress in H4IIE hepatoma cells as evidenced by a marked decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 32 publications
5
78
0
Order By: Relevance
“…The current experiments demonstrate that Keap1 complex disruption in vivo occurs through an Erk-and p38-independent mechanism, thereby ruling out an Erk-or p38-dependent phosphorylation event as the proximate triggering signal (45). Other kinases such as protein kinase C (53) and phosphatidylinositol 3-kinase (54,55) have also been implicated in Nrf2 induction, leaving open the possibility that kinases activated by oxidant exposure provide the initiating signal for Keap1 complex disruption and Nrf2 release, although this remains to be demonstrated.…”
Section: Figmentioning
confidence: 99%
“…The current experiments demonstrate that Keap1 complex disruption in vivo occurs through an Erk-and p38-independent mechanism, thereby ruling out an Erk-or p38-dependent phosphorylation event as the proximate triggering signal (45). Other kinases such as protein kinase C (53) and phosphatidylinositol 3-kinase (54,55) have also been implicated in Nrf2 induction, leaving open the possibility that kinases activated by oxidant exposure provide the initiating signal for Keap1 complex disruption and Nrf2 release, although this remains to be demonstrated.…”
Section: Figmentioning
confidence: 99%
“…The protein binding to the ARE consensus sequence involves the Nrf proteins, as well as Maf family members (6,7). Oxidative stress induces GSTA2 via ARE activation, which involves the Nrf proteins (8,9). Transcription factors of the CCAAT/enhancer binding protein (C/EBP) family play roles in cell differentiation and exert their function by regulating the expression of tissue-specific genes, as well as cell proliferation (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Results from the functional studies consistently showed that inhibition of the PI3K/Akt pathway decreased NRF2 activation induced by a variety of stimuli in different cell lines, while expression of a constitutive active mutant of Akt increased NRF2 activity, indicating that PI3K/Akt signalling is a positive regulator of NRF2 (Chen et al, 2009;Jain and Jaiswal, 2006;Kang et al, 2000;Lee et al, 2001;Wang et al, 2008). PI3K/Akt controls NRF2 via multiple indirect mechanisms.…”
Section: Signaling Pathways That Regulate Nrf2 Activationmentioning
confidence: 91%